Faktor Prediktor Terjadinya Depresi Postpartum di Rumah Sakit Panti Rapih Yogyakarta - Agnes Mahayanti; Intansari Nurjannah; Widyawati (STIKes Panti Rapih, 2020)
Background: The postpartum period was a physical and psychological adaptation process. Psychological disturbances could present in form of postpartum blues, postpartum depression, and postpartum psychosis. Objective: The objective of this research was to determine the incidence of postpartum depression, identify predictors of postpartum depression and identify the dominant predictors of postpartum depression. Methods: this research used a cross sectional design. Sample were pregnant women which were chosen by random sampling technique. Data was collected with questionnaire to measure the predictors of postpartum depression was carried out with the Revision Postpartum Depression Predictors Inventory (PDPI) questionnaire and to measure depression scores used with the Edinburgh Postnatal Depression Scale (EPDS). Data analysis was done by univariate and bivariate analysis with with chi-square statistical tests and multivariate with logistic regression tests. Results: The results showed that the significant predictors were economic status, self-esteem, marital satisfaction, postpartum blues, and prenatal depression. The dominant predictor factor is satisfaction in marriage with a t value of 2.778 times. Conclusion: The results of the study show that marital satisfaction is a dominant predictor of postpartum depression, indicating that marital satisfaction or relationship quality is one of the important support systems because of the need for partner involvement in care actions during the pregnancy period until with the puerperium as efforts to prevent postpartum depression. Keywords: postpartum depression, postpartum period, postpartum bues